The Hardness Effect of Friction Stir Welding by MILKO 37 Milling Machine - M., Ishak; M. A. H. M., Jasri; M., Afendi; A., Ismail (2015)
This study investigates the mechanical properties of aluminium A5083 in terms of hardness after it has been welded by friction stir welding (FSW) process. In this study, MILKO 37 milling machine was modified to run FSW process on 4 mm aluminium A5083 plate butt joint. In the experiments, variables of travel speed and tool rotational speed based on capability of machine were used. From previous researches, the tool geometry design is one of the major parameters for FSW process. Therefore, tool geometry design was initially determined based on trial and error. The tool geometry chosen was solid cylinder as the effect toward the FSW process was minimal. The design shows that the pin length should be 80-95 % of plate thickness and the pin probe diameter shape is cylinder flat base. The tool’s material chosen was a high carbon steel grade A709 with hardening process using standard ASTM A709 GR 50/type 1.